Reproduction uniparentale et polyploidie induites chez la truite arc-en-ciel (Oncorhynchus mykiss) et chez les bivalves Crassostrea gigas, Ruditapes philippinarum et Chlamys varia - Diter, Alain (Université Paris 6, 1990)
Methods of gynogenesis, androgenesis and polyploidy induction were developed with the aim of genetic improvement in the rainbow trout, the Pacific oyster, the Manila clam and the black scallop. In the trout: · haploid androgenesis was induced by means of a pressure shock applied on diploid eggs, probably at the time of karyogamy. Diploid androgenetic individuals were directly produced from eggs fertilized with sperm from tetraploid male. · a heat shock treatment effective for suppressing the first egg mitosis was developed. This treatment allows the production of homozygous gynogenetic lines (checked using enzyme electrophoresis technique) from eggs inseminated with ultraviolet irradiated sperm. The treatment also induced tetraploidy in eggs normally fertilized by functional sperm. In the molluscs : · triploidy was induced by egg treatment with cytochalasin B in the Manila clam and the black scallop. Triploidy did not reduced the growth rate during the larval stages. In the Manila clam, gametogenesis was retarded by triploidy but the sex-ratio remained apparently unchanged. · tetraploidy induction was attempted in the Pacific oyster using a pressure shock, and in the Manila clam by the use of cytochalasin B. Resulting tetraploid embryos proved to be inviable. However the pressure shock treatment could still be optimized. · gynogenesis was induced in the Pacific oyster in eggs inseminated by ultraviolet irradiated sperm. Cytochalasin B treatments of these eggs resulted in diploid and tetraploid gynogenetic embryos. The viability of such individuals is not still established. Mechanisms which could lead to the tetraploidization of gynogenetic eggs are discussed. A des fins d'amélioration génétique, des méthodes d'induction de la gynogenèse, de l'androgenèse et de la polyploïdie ont été développées chez la truite arc-en-ciel, l'huître creuse, la palourde japonaise et le pétoncle noir. Chez la truite : · l'androgenèse haploïde a été induite par un choc de pression appliqué sur des oeufs diploïdes, probablement au ...